The automotive chassis : engineering principles : chassis and vehicle overall, wheel suspensions and types of drive, axle kinematics and elastokinematics, steering, springing, tyres, construction and calculations advice /: engineering principles : chassis and vehicle overall, wheel suspensions and types of drive, axle kinematics and elastokinematics, steering, springing, tyres, construction and calculations advice. (2001) - Unknown
No abstract available